A Sonatina para Flauta e Violão de Radamés Gnattali: estudo de aspectos estruturais e interpretativos do primeiro movimento - Raissa Anastasia de Souza Melo (2007)
The present article has as purpose an analytic and interpretative survey of the first movement from Sonatina for flute and guitar of Radamés Gnattali. The methodological procedure used was one that focused on the score analysis and the analysis of three recordings of this work. The analysis was focused on the structural and formal elements of the musical discourse which provided subsidies to the best understanding of Gnattalis compositional style. While comparing the recordings it was observed the way with which each duo of interpreters understands and brings to the world of the sounds their own conception of the Sonatina. This article also discusses the relationship between the interpreter and the work, as well as it attempts a definition of musical analysis.